2020
DOI: 10.1002/jum.15304
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis of Ultrasound Images to Differentiate Simple Fibroadenomas From Complex Fibroadenomas and Benign Phyllodes Tumors

Abstract: and Data System (BI-RADS) category 4A lesions can be distinguished from BI-RADS 3 lesions with main ultrasound (US) findings such as a well-defined contour, round/oval shape, and parallel orientation with a homogeneous echo pattern. Breast Imaging Reporting and Data System 4A solid masses might be diagnosed as simple fibroadenomas (SFAs), complex fibroadenomas (CFAs), or benign phyllodes tumors (BPTs). Complex fibroadenomas have an increased risk of invasive cancer development than SFAs, and BPTs have a risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…1 In another study, a complex-cystic echo pattern was also reported in most CFAs. 7 Despite these, an irregular shape, a noncircumscribed contour, microcalcification content, and posterior acoustic enhancement are more common in CFAs than SFAs. In some cases, the imaging findings are challenging.…”
Section: B-mode Ultrasound Features Of Cfasmentioning
confidence: 99%
See 3 more Smart Citations
“…1 In another study, a complex-cystic echo pattern was also reported in most CFAs. 7 Despite these, an irregular shape, a noncircumscribed contour, microcalcification content, and posterior acoustic enhancement are more common in CFAs than SFAs. In some cases, the imaging findings are challenging.…”
Section: B-mode Ultrasound Features Of Cfasmentioning
confidence: 99%
“…22 The mean size of SFAs is smaller than that of CFAs. 1,7,23 In the literature, there is a hypothesis that larger fibroadenomas have stiffer structures than smaller ones because of prominent compression of Figure 5. Routine US evaluation of a 32-year-old female patient.…”
Section: Elastographic Features Of Cfasmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep learning and other technologies of artificial intelligence (AI) can accurately identify lesions in images, calculate and obtain quantitative information on the morphology and textural features of lesions, and thus provide a basis for differentiating breast diseases (10,11). Presently, studies on AI for differentiating PTs from FAs are limited and have mainly focused on MRI and ultrasonic images (12)(13)(14). Research has shown that the textural features on MRI T2-weighted short-tau inversion recovery (T2W-STIR) have higher diagnostic performance compared with clinical and conventional MRI features for distinguishing between PTs and FAs (12).…”
Section: Introductionmentioning
confidence: 99%